Influência do acabamento superficial obtido por fresamento de topo esférico na resistência à cavitação de um revestimento austenítico depositado por MIG - Marczal, Mauricio Daniel (2019)
The cavitation phenomenon, which occurs in hydraulic turbines, represents a serious efficiency problem related to the maintenance of hydrogenerators. High repair times associated with total equipment outages that significantly impact the effective cost of turbine maintenance. Welding processes are normally used in the current scenario when equipment recovery is required, and are accompanied by grinding finish, usually without control, only with operator observation, which uses various surface irregularities, causing changes deduced and not homogeneous in the roughness profile, which in turn affects the resistance to cavitation. Understanding the effects of cavitation, the effects associated with blocked surfaces at different usage parameters become necessary to improve maintenance actions, enabling the application of upgrade techniques to recover damaged damage. The present research evaluated the roughness profiles applied by different coating parameters in a cavitation resistant austenitic coating and its influence on cavitation mass loss, relating to different variations generated with cavitation resistance. The results indicate that the surface finish used by machining influences the cavitation process mainly during the incubation period, developing mainly with the pitting training mechanism in non-preferential regions, erosion of micro-burr regions with material organization adhered to machining use. It also has to be considered that the surface generated by a head tool interchangeable at lower cutting speed and advancing by lower tooth was a process that caused the erosion process more slowly.